2019
DOI: 10.3390/s19163508
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Ozone Sensor Based on Selective Oxidation of Methylene Blue in Mesoporous Silica Films

Abstract: Sensitive and selective personal exposure monitors are needed to assess ozone (O3) concentrations in the workplace atmosphere in real time for the analysis and prevention of health risks. Here, a cumulative gas sensor using visible spectroscopy for real-time O3 determination is described. The sensing chip is a mesoporous silica thin film deposited on transparent glass and impregnated with methylene blue (MB). The sensor is reproducible, stable for at least 50 days, sensitive to 10 ppb O3 (one-tenth of the occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The methylene blue-based sensor was relatively low cost and rapid, suitable for workers as a real-time analytical instrument. 154…”
Section: Personal Safety Devicesmentioning
confidence: 99%
“…The methylene blue-based sensor was relatively low cost and rapid, suitable for workers as a real-time analytical instrument. 154…”
Section: Personal Safety Devicesmentioning
confidence: 99%
“…For the purpose of this research, in order to determine real-time O 3 , a cumulative gas sensor is shown in [ 66 ]. Such a sensor used visible spectroscopy, which was based on cheap material, and was aimed at carrying out O 3 measurements in workplaces using a portable device.…”
Section: Some General Comments On Ozone Sensors: Characteristics Amentioning
confidence: 99%
“…However, it is not enough to design a sensor that measures the value of a certain physical quantity; this measurement must also be as robust as possible against disturbances and unwanted information. In this sense, several authors [ 66 , 67 ] are also concerned about the robustness that the sensors could have and are aware of the limitations of the sensor as an isolated element. Therefore, to achieve a good design of measurement equipment, it is necessary to put the sensor inside a signal conditioning and processing system that is capable of dealing with everything that represents noise, disturbance, and unwanted information [ 73 ].…”
Section: Some General Comments On Ozone Sensors: Characteristics Amentioning
confidence: 99%
“…Mesoporous oxide films are materials with technological relevance in sensing, [ 1 ] molecular sieving, [ 2 ] catalysis, and energy conversion. [ 3 ] All these technologies depend on molecular transport in nanoscale pores.…”
Section: Introductionmentioning
confidence: 99%